Hydrogen‐rich water ameliorates bronchopulmonary dysplasia (BPD) in newborn rats. Issue 9 (4th February 2016) - Muramatsu, Yukako; Ito, Mikako; Oshima, Takahiro; Kojima, Seiji; Ohno, Kinji
Summary: Bronchopulmonary dysplasia (BPD) is characterized by developmental arrest of the alveolar tissue. Oxidative stress is causally associated with development of BPD. The effects of hydrogen have been reported in a wide range of disease models and human diseases especially caused by oxidative stress. We made a rat model of BPD by injecting lipopolysaccharide (LPS) into the amniotic fluid at E16.5. The mother started drinking hydrogen‐rich water from E9.5 and also while feeding milk. Hydrogen normalized LPS‐induced abnormal enlargement of alveoli at P7 and P14. LPS increased staining for nitrotyrosine and 8‐OHdG of the lungs, and hydrogen attenuated the staining. At P1, LPS treatment decreased expressions of genes for FGFR4, VEGFR2, and HO‐1 in the lungs, and hydrogen increased expressions of these genes. In contrast, LPS treatment and hydrogen treatment had no essential effect on the expression of SOD1. Inflammatory marker proteins of TNFα and IL‐6 were increased by LPS treatment, and hydrogen suppressed them. Treatment of A549 human lung adenocarcinoma epithelial cells with 10% hydrogen gas for 24 hr decreased production of reactive oxygen species in both LPS‐treated and untreated cells. Lack of any known adverse effects of hydrogen makes hydrogen a promising therapeutic modality for BPD.Pediatr Pulmonol. 2016; 51:928–935 . © 2016 Wiley Periodicals, Inc.